The “Kakek Nenek Asuh” Program increases Community Knowledge about Stunting and Nutrition for Children under five in Sengon Village. - Ning Arti Wulandari; Yeni Kartika Sari; Miftah Chairunnisa (UNUSA Press, 2022)
The high number of stunting children in Indonesia is still a severe problem that can impact the quality of human resources. The foster grandparent's program is one of the ways that servants do to overcome these problems. This service activity aims to increase the productive community's knowledge about stunting and improve the nutrition of children under five in Sengon Village. This service is aimed at 110 respondents who participate in Posbindu in Sengon Village, Bendungan District, Trenggalek Regency, as a foster grandparents program. The activity begins with providing education about stunting to increase public knowledge. The instruments used were leaflets, booklets about stunting and power points delivered using an LCD and projector screen. After education is given, the knowledge of the elderly will be measured again. Furthermore, the elderly will be allowed to apply their knowledge to educate their families and surroundings who have children under five with poor nutritional status and stunting. The toddler's weight will be measured again one month later. The data will be analyzed using the Wilcoxon Sign Rank Test. The service results showed that the foster grandparent's program affected the knowledge of the elderly about stunting and under-five nutrition with p=0.00. So it is recommended that the foster grandparent's program continue to be carried out so that the nutrition of children under five is increased and the number of stunting children under five decreases.